Child Education: achievements and challenges in overcoming welfare (Research, Society and Development, 2022)
The present work aims to analyze the achievements and challenges facing the overcoming of the welfare character in Early Childhood Education. To achieve the proposed objective, we stop to rescue the history of Early Childhood Education from its origin, linked to the Industrial Revolution, to the achievements in the context of public educational policies. The theoretical approach has as main authors Dias, Didonet, Kuhlmann Jr., Marcilio and Paschoal and Machado, which deal with the historical context of Early Childhood Education and the right of young children to education. From the methodological point of view, it is a qualitative research, with an exploratory and documentary nature. Regarding the results, we infer that the care for young children, outside the family, appears in the context of the development of capitalism and industrialization. Early Childhood Education, in turn, has its origins marked by assistentialism, strongly characterized by the custody, care, feeding and hygiene of young children. Faced with this reality, it was possible to verify that, despite the advances in favor of guaranteeing a quality education as a subjective right of the young child, there are still many challenges to be faced and many advances to be achieved in favor of the effectiveness of the public policies in Early Childhood Education.